Development of Understanding Test Instruments for Grade 7 Junior High School Students on Temperature, Heat and Expansion Topics - Fibriyana Safitri; Dadi Rusdiana; Achmad Samsudin; Arif Widiyatmoko (Jurnal Penelitian Pendidikan IPA, 2025)
The aim of this research is to analyze the validity, reliability, level of difficulty and differentiating power of understanding test items, especially on the temperature, heat and expansion topic that has been developed. The test items consist of 20 multiple choice questions which refer to cognitive process of understanding according to Revised Bloom’s Taxonomy. The subjects of this research were 31 students in class VIII of junior high school. Before being tested on students, the understanding test items were evaluated by 5 experts. The method used to analyze validity, reliability, level of difficulty and differentiating power of items is the Rasch model using MINISTEP software version 4.3.1. The results of the analysis show that the understandingtest items on temperature, heat and expansion can be used to test students' understanding. Validity analysis results using item fit criteria with output in the form of MNSQ and ZSTD values.  Meanwhile, the value of reliability item of 0.88 indicates that the quality of the items in the understanding instrument is included in the good category. On the other hand, the distribution of the difficulty level of items is uneven, there are more items in the difficult category than items in the easy category. However, 10 items have a differentiating power of more than 0.40 which is included in the very good category, so that they can differentiate students with high and low understanding very well.